SEGMENTATION OF CONSUMERS IN JAKARTA RELATED TO THE FOOD SAFETY ISSUE - Renita Sagara; Dahlia Darmayanti (Journal of Business Strategy and Execution, 2009)
The objectives of this thesis are to (1) identify the most significant factors that affect consumers’ attitudes toward food safety issue in Jakarta, (2) segment the market based on the factors identified, and (3) characterize each segment based on their demographic factors. 300 questionnaires regarding the food safety issue were distributed to 5 major regions in Jakarta. Firstly, frequency analysis was used to profile the respondents, then the data gathered was subjected to factor analysis to discover the most significant factors from the responses. After that, descriptive analysis was used to identify the means and standard deviation to further be used in identifying cluster characteristics. Next, cluster analysis was used to cluster/segment the respondents based on the factor analysis. Finally, cross tabulation was used to identify the demographic factors that dominate each cluster. It was found that consumer food safety attitudes are based on 6 significant factors, which are trust towards the actors in the food supply chain; concern about the content of the food eaten; acceptance of the number of food-borne disease outbreaks and people falling ill and/or dying due to the outbreaks; regulations of the government; concern about the safety of the foods bought from stores and restaurants, and preference for the right to buy foods no matter how safe or unsafe they might be. From the 6 factors, 4 segments of consumers were identified, namely, “Independent”, “Trusting”, “Apprehensive”, and “Nonchalant”. It is concluded that there is a relationship between education level and trust level, and among income levels, age and concern levels. Highly educated people most definitely have a favourable level of trust, while less educated people do not. Also, older people with lower incomes are most definitely unconcerned about the food they eat, while younger people with higher incomes are.